An unusual case of pneumatic nail gun scrotal injury and revision of the literature - Leonardo Bizzotto (Archivio Italiano di Urologia e Andrologia, 2017)
Pneumatic nail guns are hand-held tools commonly utilized in both industrial and non occupational setting. These devices facilitate production and boost efficiency but also can be a potential cause of serious injuries. Nail guns are the most frequent tool associated trauma with hospitalization among construction workers. The most common sites of injuries are the hand or fingers followed by the lower extremities. We report the first case in literature of a work nail gun injury to male external genitalia.